Pemberdayaan Kelompok Peternak Lebah Di Kampung Madu Dusun Purworejo Desa Bringin Kabupaten Kediri - Marlan, Monica Widi; Prathama, M.Si, Drs. Ananta (Institut Riset dan Pengembangan Indonesia, 2023)
This research aims to determine the stages of empowering groups of honey beekeepers by taking research sites in Kampung Madu,Purworejo Bringin’s Village, District of Badas, Kediri Regency. This is a descriptive qualitative study using the technique of data collection namely, observation, interview, and documentation. The focus of this research is based on three stages of empowerment by Wrihatnolo and Dwijowijoto they are: (1) Awarness Stage; (2) Capacity Building; (3)Empowerment Stage. The research found out that 1. The process of the awareness and assistance to beekeeper’s has been carried out well, because it is carried out on ongoing basis; 2. An increase of the beekeeper skill’s, a variation of honey product’s, and also an awareness from beekeeper’s to develeop their product with creating a label; 3.Promoting Purworejo village as Honey Village and also Bee educational tourism village. The three stages of empowerment that have been carried out by the Bringin’s village government can be concluded that the empowerment process carried out is quite optimal.